Heterocyclic aramid nanofiber membrane and preparation method thereof

By polymerization of phenyl azhenylene, phenyl-measigo, 2- (4-aminophenyl) -5-aminophenylzole and coronal ether, regulating the methamphetamine of the hybrid aravarous aggregation induced self-assembly appearance, solve the existing existing In the technology, the problem of insufficient performance of nano -fiber membrane in the technology has realized the membrane material with excellent performance of high -pull intensity and low -agent constant, and the performance of the dielectric loss.

CN119350615AActive Publication Date: 2025-01-24TSINGHUA UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411614773.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-24
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The prior art has not yet introduced copolymerization of crown ether compounds to effectively improve the tensile strength of heterocyclic aramid nanofiber membrane and reduce its dielectric constant and dielectric loss.

Method used

By copolymerizing p-phenylenediamine, terephthaloyl chloride, 2-(4-aminophenyl)-5-aminobenzimidazole and crown ether, the polymerization-induced self-assembly morphology of heterocyclic aramid is controlled to form uniform size nanofibers and form an interlocking structure that improves the tensile strength and dielectric properties of the membrane.

Benefits of technology

The stretching strength of the miscellaneous ara -nano -fiber membrane is ≥150MPa, the dielectric constant ≤3, and the dielectric loss ≤0.01, which significantly improves the mechanical performance of the material and the dielectric performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350615A_ABST
    Figure CN119350615A_ABST
Patent Text Reader

Abstract

The invention relates to a heterocyclic aramid nanofiber membrane and a preparation method thereof, and belongs to the technical field of aramid membranes, and the heterocyclic aramid nanofiber membrane with high tensile strength, low dielectric constant and low dielectric loss is prepared by introducing crown ether compound copolymerization modification heterocyclic aramid. According to the heterocyclic aramid nanofiber membrane, crown ether is added in the polymerization process to participate in copolymerization, the polymerization-induced self-assembly behavior in the heterocyclic aramid polymerization process is regulated and controlled according to the principle that crown ether and amino can form hydrogen bond interaction, and crown ether can be nested on a heterocyclic aramid chain segment through hydrogen bond interaction; the shape of the heterocyclic aramid nanofiber is regulated and controlled, the obtained nanofiber is uniform in size, an interlocking structure is easily formed among the fibers, the tensile strength of a film can be improved, crown ether nested on a chain segment plays a role of a plasticizer and can improve the toughness of the film, and meanwhile, the free volume of a polymer is increased by introduction of crown ether; and the dielectric property of the film material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aramid membranes, and in particular to a heterocyclic aramid nanofiber membrane and a preparation method thereof. Background Art

[0002] With the rapid growth of the electronic information industry, especially with the advent of the 5G era, the demand for materials in the high-end electronic information field has become increasingly stringent. The development of ultra-large-scale integrated circuits has put forward higher performance standards for low-dielectric materials, including excellent strength, higher thermal stability, lower dielectric constant and dielectric loss.

[0003] Heterocyclic aramid is a high-performance polymer copolymerized by p-phenylenediamine, terephthaloyl chloride and heterocyclic monomers, also known as "aromatic III" or "F-12". Heterocyclic aramid has the characteristics of light weight, high strength, high thermal stability and flame retardancy, making it promising for application in low dielectric polymer materials. How to further improve the mechanical properties of aramid materials and reduce their dielectric constant, dielectric loss and other properties is an important research direction.

[0004] At present, researchers have explored a variety of methods to improve the performance of aramid materials, including surface modification technology, introduction of nanofillers, introduction of other monomer copolymerization methods, etc. However, there is no method to improve the performance of aramid materials by introducing crown ether copolymerization and adjusting the polymerization-induced self-assembly morphology of heterocyclic aramid nanofibers. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide a heterocyclic aramid nanofiber membrane and a preparation method thereof, so as to solve the problem that there is currently no method for preparing a heterocyclic aramid nanofiber membrane with high tensile strength, low dielectric constant and low dielectric loss by introducing crown ether compounds to copolymerize and modify heterocyclic aramid.

[0006] In a first aspect, the present invention provides a heterocyclic aramid nanofiber membrane, wherein the heterocyclic aramid nanofiber membrane is obtained by copolymerization of p-phenylenediamine, terephthaloyl chloride, 2-(4-aminophenyl)-5-aminobenzimidazole and crown ether.

[0007] Furthermore, the heterocyclic aramid nanofiber membrane has nanofibers of uniform size, and the nanofibers form an interlocking structure.

[0008] Furthermore, the heterocyclic aramid nanofiber membrane has a tensile strength of ≥150 MPa, a dielectric constant of ≤3, and a dielectric loss of ≤0.01.

[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned heterocyclic aramid nanofiber membrane, comprising the following steps:

[0010] (1) adding a dissolving salt and a crown ether to a polymerization organic solvent, adding p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole under a protective gas atmosphere, and stirring until dissolved to obtain a mixture system;

[0011] (2) adding terephthaloyl chloride to the mixture system under a protective gas atmosphere, stirring at a high speed to cause a polymerization reaction, and stopping the reaction when the Weissenberg effect appears to obtain a heterocyclic aramid nanofiber polymerization liquid;

[0012] (3) The heterocyclic aramid nanofiber polymer solution is used as a casting solution, the casting solution is subjected to vacuum degassing treatment, coated into a film, added into a coagulation bath for immersion, and dried to obtain the heterocyclic aramid nanofiber membrane.

[0013] Furthermore, in step (1), the dissolution-aiding salt includes one or more of lithium chloride, calcium chloride, lithium bromide or calcium bromide;

[0014] And / or, the crown ether includes one or more of 12-crown-4, 15-crown-5, 18-crown-6, 2-benzo-21-crown-7, and 2-benzo-24-crown-8;

[0015] And / or, the polymerization organic solvent is one or more of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, and 2-methyl-1-pyrrolidinylcyclopropanone.

[0016] Furthermore, step (1) also includes removing water from the polymerization organic solvent.

[0017] Furthermore, in step (1), the mass fraction of the solubilizing salt in the polymerization organic solvent is 2 to 10%;

[0018] and / or, the total molar ratio of the crown ether to p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole is 0.1 to 1:1;

[0019] and / or, the molar ratio of p-phenylenediamine to 2-(4-aminophenyl)-5-aminobenzimidazole is 3:7 to 8:2;

[0020] The total molar concentration of the p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole in the mixed system is 0.1-0.3 mol / L.

[0021] Furthermore, in step (2), the total molar ratio of the terephthaloyl chloride to the p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole in step (1) is 1.001 to 1.007:1.

[0022] Furthermore, in step (2), the speed of high-speed stirring is 1000-2000 rpm, and the temperature of the polymerization reaction is 0-5°C.

[0023] Furthermore, in step (2), the diameter of the heterocyclic aramid nanofibers in the heterocyclic aramid nanofiber polymer solution is 3 to 10 nm.

[0024] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0025] (1) The heterocyclic aramid nanofiber membrane of the present invention is copolymerized by adding crown ethers during the polymerization process, and the polymerization-induced self-assembly behavior during the polymerization of heterocyclic aramid is regulated by the principle that the crown ethers can form hydrogen bond interactions with amino groups. The crown ethers can be nested in the heterocyclic aramid chain segments through hydrogen bond interactions, thereby regulating the morphology of the heterocyclic aramid nanofibers, making the obtained nanofibers uniform in size, and easily forming an interlocking structure between the fibers, which can improve the tensile strength of the membrane. The crown ethers nested in the chain segments act as a plasticizer, which can improve the toughness of the membrane. At the same time, the introduction of the crown ethers increases the free volume of the polymer, which can improve the dielectric properties of the membrane material. The heterocyclic aramid nanofiber membrane has a tensile strength of ≥150MPa, a dielectric constant of ≤3, and a dielectric loss of ≤0.01;

[0026] (2) The heterocyclic aramid nanofibers of the present invention utilize crown ethers to regulate the self-assembly behavior of aramid chain segments during the polymerization process, so that the heterocyclic aramid nanofibers have a regular and uniform morphology, and the tensile strength and dielectric properties of the obtained heterocyclic aramid nanofiber membrane material are significantly improved. The present invention utilizes the supramolecular self-assembly principle of crown ethers and amino-containing polymers to regulate the morphology of heterocyclic aramid polymer chain segments, and then regulates the performance of the material. The method described is used to prepare a heterocyclic aramid membrane with high tensile strength, low dielectric constant, and low dielectric loss. The heterocyclic aramid polymerization is regulated by copolymerization with crown ethers to obtain a heterocyclic aramid membrane material with excellent performance.

[0027] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0029] Figure 1 This is a real photo of the heterocyclic aramid nanofiber polymer solution prepared in Example 1 of the present invention;

[0030] Figure 2 This is a real photo of the heterocyclic aramid nanofiber membrane prepared in Example 1 of the present invention;

[0031] Figure 3 TEM image of the heterocyclic aramid nanofiber polymer solution prepared in Example 1 of the present invention;

[0032] Figure 4 This is a SEM image of the heterocyclic aramid nanofiber membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0034] A specific embodiment of the present invention discloses a heterocyclic aramid nanofiber membrane, which is obtained by copolymerization of p-phenylenediamine, terephthaloyl chloride, 2-(4-aminophenyl)-5-aminobenzimidazole and crown ether.

[0035] In a specific embodiment, the heterocyclic aramid nanofiber membrane has nanofibers of uniform size, and the nanofibers form an interlocking structure.

[0036] In a specific embodiment, the heterocyclic aramid nanofiber membrane has a tensile strength of ≥150 MPa, a dielectric constant of ≤3, and a dielectric loss of ≤0.01.

[0037] Preferably, the tensile strength of the heterocyclic aramid nanofiber membrane is 150-300 MPa, for example, 150 MPa, 160 MPa, 170 MPa, 180 MPa, 190 MPa, 200 MPa, 210 MPa, 220 MPa, 230 MPa, 240 MPa, 250 MPa, 260 MPa, 270 MPa, 280 MPa, 290 MPa, 300 MPa, and the dielectric constant is 2-3, for example, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0.

[0038] The heterocyclic aramid nanofiber membrane of the present invention participates in copolymerization by adding crown ethers during the polymerization process, and uses the principle that the crown ethers can form hydrogen bond interactions with amino groups to regulate the polymerization-induced self-assembly behavior during the polymerization of the heterocyclic aramid. The crown ethers can be nested in the heterocyclic aramid chain segments through hydrogen bond interactions, thereby regulating the morphology of the heterocyclic aramid nanofibers, making the obtained nanofibers uniform in size, and easily forming interlocking structures between the fibers, which can improve the tensile strength of the membrane. The crown ethers nested in the chain segments act as a plasticizer, which can improve the toughness of the membrane. At the same time, the introduction of the crown ethers increases the free volume of the polymer, which can improve the dielectric properties of the membrane material.

[0039] Another specific embodiment of the present invention discloses a method for preparing the above heterocyclic aramid nanofiber membrane, comprising the following steps:

[0040] (1) adding a dissolving salt and a crown ether to a polymerization organic solvent, adding p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole under a protective gas atmosphere, and stirring until dissolved to obtain a mixture system;

[0041] (2) adding terephthaloyl chloride to the mixture system under a protective gas atmosphere, stirring at a high speed to cause a polymerization reaction, and stopping the reaction when the Weissenberg effect appears to obtain a heterocyclic aramid nanofiber polymerization liquid;

[0042] (3) The heterocyclic aramid nanofiber polymer solution is used as a casting solution, the casting solution is subjected to vacuum degassing treatment, coated into a film, added into a coagulation bath for immersion, and dried to obtain the heterocyclic aramid nanofiber membrane.

[0043] The method of the invention uses p-phenylenediamine, terephthaloyl chloride, 2-(4-aminophenyl)-5-aminobenzimidazole and 18-crown ether-6 for low-temperature copolymerization to obtain a heterocyclic aramid nanofiber solution, and the obtained polymer solution is coated by a scraper, and then solvent exchange is carried out in deionized water to obtain a self-supporting wet film, and the self-supporting wet film is washed and hot-pressed to obtain a heterocyclic aramid film with high tensile strength, low dielectric constant and low dielectric loss; the heterocyclic aramid nanofiber uses crown ether to regulate the self-assembly behavior of aramid chain segments during the polymerization process, so that the heterocyclic aramid nanofiber has a regular and uniform morphology, and the tensile strength and dielectric properties of the obtained heterocyclic aramid film material are significantly improved. The present invention utilizes the supramolecular self-assembly principle of crown ether and amino-containing polymer to regulate the morphology of heterocyclic aramid polymer chain segments, thereby regulating the performance of the material. The method is used to prepare a heterocyclic aramid film with high tensile strength, low dielectric constant and low dielectric loss. The polymerization of heterocyclic aramid is regulated by copolymerization with crown ether to obtain a heterocyclic aramid film material with excellent performance.

[0044] In a specific embodiment, in step (1), the dissolution-advantage salt includes one or more of lithium chloride, calcium chloride, lithium bromide or calcium bromide;

[0045] And / or, the crown ether includes one or more of 12-crown-4, 15-crown-5, 18-crown-6, 2-benzo-21-crown-7, and 2-benzo-24-crown-8;

[0046] And / or, the polymerization organic solvent is one or more of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, and 2-methyl-1-pyrrolidinylcyclopropanone.

[0047] When multiple crown ethers or polymeric organic solvents are selected, they can be mixed in any proportion.

[0048] In a specific embodiment, step (1) further comprises dehydrating the polymer organic solvent. Specifically, the molecular sieve is heated at 200-400°C for 4-8h, the polymer organic solvent is added, and the mixture is naturally cooled to room temperature to obtain a dehydrated polymer organic solvent.

[0049] Specifically, the water content in the dewatered polymer organic solvent is less than 100 ppm.

[0050] It should be noted that, since the terephthaloyl chloride monomer in the polycondensation reaction of heterocyclic aramid is extremely sensitive to water and can react with water to generate terephthalic acid and hydrochloric acid, it is necessary to fully remove water from the solvent.

[0051] In a specific embodiment, in steps (1) and (2), the protective gas is nitrogen.

[0052] In a specific embodiment, in step (1), the mass fraction of the solubilizing salt in the polymerization organic solvent is 2 to 10%, for example, 2%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10%;

[0053] It should be noted that when there is too little solubilizing salt, as the polymerization process proceeds, the gradually growing polymer molecular segments cannot be stable in the polymerization organic solvent, which will cause the polymer to precipitate in the polymerization organic solvent when the molecular weight is low, resulting in polymerization failure. When the solubilizing salt content is too high, since the solubilizing salt easily absorbs water to form a solubilizing salt-hydrate compound, it will cause side reactions in the polymerization and make the polymerization effect worse.

[0054] And / or, the total molar ratio of the crown ether to p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole is 0.1 to 1:1, for example, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1.

[0055] And / or, the molar ratio of p-phenylenediamine to 2-(4-aminophenyl)-5-aminobenzimidazole is 3:7-8:2, for example, 3:7, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1. The above molar ratio can generate a heterocyclic aromatic structure without producing other side reactions. The total molar concentration of p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole in the mixed system is 0.1-0.3 mol / L, for example, 0.1 mol / L, 0.12 mol / L, 0.14 mol / L, 0.16 mol / L, 0.18 mol / L, 0.20 mol / L, 0.22 mol / L, 0.24 mol / L, 0.26 mol / L, 0.28 mol / L, 0.3 mol / L.

[0056] In a specific embodiment, in step (2), the total molar ratio of terephthaloyl chloride to p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole in step (1) is 1.001 to 1.007:1, for example, 1.001:1, 1.002:1, 1.003:1, 1.004:1, 1.005:1, 1.006:1, 1.007:1.

[0057] In a specific embodiment, in step (2), the speed of high-speed stirring is 1000-2000 rpm, for example, 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm, 1500 rpm, 1600 rpm, 1700 rpm, 1800 rpm, 1900 rpm, 2000 rpm, and the temperature of the polymerization reaction is 0-5°C, for example, 0°C, 0.5°C, 1°C, 1.5°C, 2°C, 2.5°C, 3°C, 3.5°C, 4°C, 4.5°C, 5°C.

[0058] In a specific embodiment, in step (2), the diameter of the heterocyclic aramid nanofibers in the heterocyclic aramid nanofiber polymer solution is 3 to 10 nm, preferably, the diameter is 4 to 6 nm.

[0059] In a specific embodiment, in step (3), the coagulation bath is one or more of water, ethanol, propanol, acetone, butanone or tert-butanol.

[0060] Specifically, after the heterocyclic aramid nanofiber polymer solution is diluted, a casting solution with a certain solid content is obtained, and the casting solution is subjected to a vacuum degassing treatment. After all the bubbles in the casting solution are eliminated, a scraper is used to scrape and form a film, and the resulting scraped film is peeled off and transferred to a coagulation bath for immersion for a certain period of time, so that the solvent and the coagulation bath are fully exchanged to obtain a self-supporting heterocyclic aramid nanofiber wet film, and the heterocyclic aramid nanofiber wet film is vacuum hot-pressed to obtain a heterocyclic aramid nanofiber membrane with high tensile strength, low dielectric constant and low dielectric loss.

[0061] Furthermore, step (3) further comprises diluting the heterocyclic aramid nanofiber polymer solution with the polymer organic solvent described in step (1) to obtain a casting solution.

[0062] Preferably, the heterocyclic aramid nanofiber polymer solution is diluted to a mass fraction of 50-100% of the original solution, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%.

[0063] In step (3), the immersion time is 6 to 72 hours, for example, 6 hours, 10 hours, 14 hours, 18 hours, 22 hours, 24 hours, 28 hours, 32 hours, 36 hours, 40 hours, 44 hours, 48 ​​hours, 52 hours, 56 hours, 60 hours, 64 hours, 68 hours, 72 hours. The above immersion time can ensure sufficient exchange of the solvent. After the immersion is completed, wash with deionized water for 3 to 10 times, for example, 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, 10 times, to ensure that impurities on the surface of the membrane are completely cleaned.

[0064] Specifically, in step (3), the drying is vacuum drying, the drying temperature is 60-150°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, and the drying time is 0.5-2h, for example, 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h.

[0065] The technical solution of the present invention is further explained below in conjunction with specific examples. It should be noted that the two diamines described below are p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole.

[0066] Example 1

[0067] A method for preparing a heterocyclic aramid nanofiber membrane of this embodiment includes the following steps:

[0068] (1) 3.5 g of LiCl and 3.965 g of 18-crown-6 (with a total molar ratio of p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole of 1:1) are added to 100 mL of N,N-dimethylacetamide, wherein the molecular sieve is heated at 400° C. for 4 h, N,N-dimethylacetamide is added, and the temperature is cooled to room temperature to obtain N,N-dimethylacetamide after dehydration, with a water content of less than 100 ppm, the polymerization system is controlled at 0° C., and two diamines with a molar concentration of 0.15 mol / L are added while nitrogen is introduced, wherein the molar ratio of p-phenylenediamine to 2-(4-aminophenyl)-5-aminobenzimidazole is 5:5, i.e., 0.811 g of p-phenylenediamine and 1.682 g of 2-(4-aminophenyl)-5-aminobenzimidazole, and the mixture is stirred at high speed until all are dissolved to obtain a mixed system;

[0069] (2) While nitrogen was introduced, 3.048 g of terephthaloyl chloride (with a total molar ratio of 1.001:1 to the two diamines) was added to the mixed system, the speed of the reaction device was adjusted to 1000 rpm, and high-speed stirring was performed until the Weissenberg effect appeared and the polymerization reaction was stopped to obtain a heterocyclic aramid nanofiber polymerization solution, wherein the theoretical mass fraction of the polymerization solution was 4.76%. The actual picture is as shown in FIG. Figure 1 As shown in the TEM image Figure 3 As shown, the nanofibers are uniform in size and form an interlocking structure;

[0070] (3) The heterocyclic aramid nanofiber polymer solution is diluted with 100 mL of N, N-dimethylacetamide to a mass fraction of 50% of the original solution to obtain a casting solution, the casting solution is subjected to vacuum degassing treatment, and then placed on a glass plate and coated with a doctor blade, with the doctor blade thickness set to 1000 μm. The resulting coated film is immersed in deionized water for 24 h to allow the polymerization solvent to be fully exchanged to obtain a self-supporting heterocyclic aramid nanofiber wet film, which is then washed with deionized water 5 times. The heterocyclic aramid nanofiber wet film is vacuum-dried at 100° C. for 1 h to obtain a crown ether-nested heterocyclic aramid nanofiber membrane with a thickness of 1000±50 μm. Figure 2 shown.

[0071] The SEM images of the crown ether nested heterocyclic aramid nanofiber membrane prepared in this example are as follows: Figure 4 As shown, the obtained membrane material has a regular morphology and a multilayer structure in cross section.

[0072] Example 2

[0073] A method for preparing a heterocyclic aramid nanofiber membrane of this embodiment includes the following steps:

[0074] (1) 10 g of CaCl2 and 0.528 g of 12-crown ether-4 (with a total molar ratio of p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole of 0.1:1) were added to 100 ml of N-methylpyrrolidone, wherein the molecular sieve was heated at 200° C. for 8 h, N-methylpyrrolidone was added, and the mixture was cooled to room temperature to obtain N-methylpyrrolidone after dehydration, with a water content of less than 100 ppm. The polymerization system was controlled at 5° C., and two diamines with a total molar concentration of 0.2 mol / L were added while nitrogen was introduced, wherein the molar ratio of p-phenylenediamine to 2-(4-aminophenyl)-5-aminobenzimidazole was 3:7, i.e., 0.973 g of p-phenylenediamine and 4.709 g of 2-(4-aminophenyl)-5-aminobenzimidazole, and the mixture was stirred at high speed until all the diamines were dissolved to obtain a mixed system;

[0075] (2) After nitrogen was introduced, 4.0807 g of terephthaloyl chloride (with a total molar ratio of 1.007:1 to the two diamines) was added to the mixed system, and the speed of the reaction device was adjusted to 2000 rpm, and the mixture was stirred at high speed until the Weissenberg effect appeared and the polymerization reaction was stopped to obtain a heterocyclic aramid nanofiber polymerization solution;

[0076] (3) The heterocyclic aramid nanofiber polymer solution is used as a casting solution, and the casting solution is subjected to vacuum degassing treatment, and then placed on a glass plate and coated with a doctor blade, and the doctor blade thickness is set to 1000 μm. The resulting coated film is immersed in ethanol for 6 hours to allow the polymerization solvent to be fully exchanged to obtain a self-supporting heterocyclic aramid nanofiber wet film, which is then washed with deionized water 10 times. The heterocyclic aramid nanofiber wet film is vacuum-dried at 150°C for 30 minutes to obtain a crown ether-nested heterocyclic aramid nanofiber membrane with a thickness of 1000±50 μm.

[0077] Example 3

[0078] A method for preparing a heterocyclic aramid nanofiber membrane of this embodiment includes the following steps:

[0079] (1) 2 g of lithium bromide and 1.101 g of 15-crown ether-5 (with a total molar ratio of p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole of 0.5:1) are added to 100 ml of N,N-dimethylformamide, wherein the molecular sieve is heated at 300° C. for 6 h, N,N-dimethylformamide is added, and the temperature is cooled to room temperature to obtain N,N-dimethylformamide after dehydration, with a water content of less than 100 ppm, the polymerization system is controlled at 5° C., and two diamines with a total molar concentration of 0.1 mol / L are added on the basis of nitrogen gas, wherein the molar ratio of p-phenylenediamine to 2-(4-aminophenyl)-5-aminobenzimidazole is 8:2, i.e., 0.865 g of p-phenylenediamine and 0.448 g of 2-(4-aminophenyl)-5-aminobenzimidazole, and the mixture is stirred at high speed until all are dissolved to obtain a mixed system;

[0080] (2) After nitrogen was introduced, 2.032 g of terephthaloyl chloride (with a total molar ratio of 1.007:1 to the two diamines) was added to the mixed system, and the speed of the reaction device was adjusted to 1800 rpm, and the mixture was stirred at high speed until the Weissenberg effect appeared and the polymerization reaction was stopped to obtain a heterocyclic aramid nanofiber polymerization solution;

[0081] (3) The heterocyclic aramid nanofiber polymer solution was diluted with 33.3 mL of N, N-dimethylformamide to a mass fraction of 75% of the original solution to obtain a casting solution. The casting solution was subjected to vacuum degassing treatment, and then placed on a glass plate and coated with a doctor blade. The doctor blade thickness was set to 1000 μm. The resulting coated film was immersed in methanol for 8 h to allow the polymerization solvent to be fully exchanged to obtain a self-supporting heterocyclic aramid nanofiber wet film. The heterocyclic aramid nanofiber wet film was washed with deionized water 7 times, and the heterocyclic aramid nanofiber wet film was vacuum-dried at 60°C for 2 h to obtain a crown ether-nested heterocyclic aramid nanofiber membrane with a thickness of 1000±50 μm.

[0082] Example 4

[0083] A method for preparing a heterocyclic aramid nanofiber membrane of this embodiment includes the following steps:

[0084] (1) 5 g of calcium bromide and 5.662 g of dibenzo-21 crown ether-7 (with a total molar ratio of p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole of 0.3:1) are added to 100 ml of 2-methyl-1-pyrrolidinylcyclopropanone, wherein the molecular sieve is heated at 250° C. for 7 h, 2-methyl-1-pyrrolidinylcyclopropanone is added, and the mixture is cooled to room temperature to obtain 2-methyl-1-pyrrolidinylcyclopropanone after dehydration, wherein the water content is less than 100 ppm, the polymerization system is controlled at 4° C., and two diamines with a total molar concentration of 0.2 mol / L are added while nitrogen is introduced, wherein the molar ratio of p-phenylenediamine to 2-(4-aminophenyl)-5-aminobenzimidazole is 6:4, i.e., 1.2985 g of p-phenylenediamine and 1.794 of 2-(4-aminophenyl)-5-aminobenzimidazole, and the mixture is stirred at high speed until all of the diamine is dissolved to obtain a mixed system;

[0085] (2) After nitrogen was introduced, 4.081 g of terephthaloyl chloride (with a total molar ratio of 1.005:1 to the two diamines) was added to the mixed system, and the speed of the reaction device was adjusted to 1500 rpm, and the mixture was stirred at high speed until the Weissenberg effect appeared and the polymerization reaction was stopped to obtain a heterocyclic aramid nanofiber polymerization solution;

[0086] (3) The heterocyclic aramid nanofiber polymer solution was diluted with 11.1 mL of 2-methyl-1-pyrrolidinyl cyclopropane to a mass fraction of 90% of the original solution, followed by vacuum degassing, and then placed on a glass plate and coated with a scraper. The scraper thickness was set to 1000 μm. The resulting scraped film was immersed in methanol for 12 h to allow the polymerization solvent to be fully exchanged to obtain a self-supporting heterocyclic aramid nanofiber wet film. The heterocyclic aramid nanofiber wet film was washed with deionized water three times, and the heterocyclic aramid nanofiber wet film was vacuum-dried at 80°C for 1.5 h to obtain a crown ether nested heterocyclic aramid nanofiber membrane with a thickness of 1000±50 μm.

[0087] Comparative Example 1

[0088] The method for preparing a heterocyclic aramid membrane in this comparative example is the same as that in Example 1, except that no crown ether is added in step (1).

[0089] Comparative Example 2

[0090] The method for preparing a heterocyclic aramid film in this comparative example is the same as that in Example 1, except that 2-(4-aminophenyl)-5-aminobenzimidazole is not added in step (1).

[0091] Comparative Example 3

[0092] The method for preparing a heterocyclic aramid membrane in this comparative example is the same as that in Example 1, except that in step (1), N,N-dimethylacetamide is not subjected to water removal treatment.

[0093] Comparative Example 4

[0094] The method for preparing a heterocyclic aramid film in this comparative example is the same as that in Example 1, except that in step (2), the polymerization temperature is 20°C.

[0095] Test Example 1

[0096] The tensile strength, dielectric constant and dielectric loss of the heterocyclic aramid nanofiber membranes prepared in Examples 1-4 and Comparative Examples 1-4, and the diameter of the nanofibers in the heterocyclic aramid nanofiber polymer solution were tested respectively. The results are shown in Table 1.

[0097] Among them, the tensile strength is tested by a universal testing machine, and the dielectric constant and dielectric loss are tested by an impedance analyzer with a frequency of 1 MHz.

[0098] Table 1

[0099] Group Tensile strength(MPa) Dielectric constant <![CDATA[Dielectric loss (×10 -3 )]]> Fiber diameter (nm) Example 1 190 3 9.75 5 Example 2 300 2.8 9 7 Example 3 250 2.5 9.8 6 Example 4 220 2 8 4 Comparative Example 1 100 3.4 20 15 Comparative Example 2 80 3.6 18 50 Comparative Example 3 90 3 25 20 Comparative Example 4 20 3 22 30

[0100] Comparative Example 1 Compared with Example 1, the tensile strength of the heterocyclic aramid film prepared without adding crown ether is significantly reduced, and the dielectric constant, dielectric loss and fiber diameter are all increased.

[0101] Comparative Example 2 Compared with Example 1, the tensile strength of the heterocyclic aramid film prepared without adding 2-(4-aminophenyl)-5-aminobenzimidazole is significantly reduced, and the dielectric constant, dielectric loss and fiber diameter are all increased.

[0102] Compared with Example 1, the aramid membranes in Comparative Examples 3 and 4 which were not prepared using the preparation method or conditions of the present invention had poor performance.

[0103] The present invention can effectively regulate the polymerization-induced self-assembly behavior of heterocyclic aramid by adding crown ether compounds to participate in the copolymerization of heterocyclic aramid, affect the morphology of heterocyclic aramid nanofibers, and thus improve the comprehensive performance of the heterocyclic aramid composite membrane.

[0104] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A heterocyclic aramid nanofiber membrane, characterized in that: The heterocyclic aramid nanofiber membrane is obtained by copolymerizing p-phenylenediamine, terephthaloyl chloride, 2-(4-aminophenyl)-5-aminobenzimidazole and crown ether.

2. The heterocyclic aramid nanofiber membrane according to claim 1, characterized in that: The heterocyclic aramid nanofiber membrane comprises nanofibers of uniform size, and an interlocking structure is formed between the nanofibers.

3. A heterocyclic aramid nanofiber membrane according to claim 1 or 2, characterized in that: The heterocyclic aramid nanofiber membrane has a tensile strength of ≥150MPa, a dielectric constant of ≤3, and a dielectric loss of ≤0.

01.

4. A method for preparing the heterocyclic aramid nanofiber membrane according to any one of claims 1 to 3, characterized in that: The steps include: (1) adding a dissolving salt and a crown ether to a polymerization organic solvent, adding p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole under a protective gas atmosphere, and stirring until dissolved to obtain a mixture system; (2) adding terephthaloyl chloride to the mixture system under a protective gas atmosphere, stirring at a high speed to cause a polymerization reaction, and stopping the reaction when the Weissenberg effect appears to obtain a heterocyclic aramid nanofiber polymerization liquid; (3) The heterocyclic aramid nanofiber polymer solution is used as a casting solution, the casting solution is subjected to vacuum degassing treatment, coated into a film, added into a coagulation bath for immersion, and dried to obtain the heterocyclic aramid nanofiber membrane.

5. The preparation method according to claim 4, characterized in that: In step (1), the dissolution-advantage salt comprises one or more of lithium chloride, calcium chloride, lithium bromide or calcium bromide; And / or, the crown ether includes one or more of 12-crown-4, 15-crown-5, 18-crown-6, 2-benzo-21-crown-7, and 2-benzo-24-crown-8; And / or, the polymerization organic solvent is one or more of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, and 2-methyl-1-pyrrolidinylcyclopropanone.

6. The preparation method according to claim 4, characterized in that: Step (1) also includes dehydrating the polymerization organic solvent.

7. The preparation method according to claim 4, characterized in that: In step (1), the mass fraction of the solubilizing salt in the polymerization organic solvent is 2 to 10%; and / or, the total molar ratio of the crown ether to p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole is 0.1 to 1:1; and / or, the molar ratio of p-phenylenediamine to 2-(4-aminophenyl)-5-aminobenzimidazole is 3:7 to 8:2; The total molar concentration of the p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole in the mixed system is 0.1-0.3 mol / L.

8. The preparation method according to claim 4, characterized in that: In step (2), the total molar ratio of the terephthaloyl chloride to the p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole in step (1) is 1.001 to 1.007:

1.

9. The preparation method according to claim 4, characterized in that: In step (2), the speed of high-speed stirring is 1000-2000 rpm, and the temperature of the polymerization reaction is 0-5°C.

10. The preparation method according to claim 4, characterized in that: In step (2), the diameter of the heterocyclic aramid nanofibers in the heterocyclic aramid nanofiber polymer solution is 3 to 10 nm.

Citation Information

Patent Citations

  • Crown ether micropore containing polyimide intrinsic microporosity polymer membrane and preparation method thereof

    CN106674560A

  • Submicron heterocyclic aramid fiber and preparation method thereof

    CN114686997A

  • Super-tough ultra-high insulating property heterocyclic aramid nanofiber film and preparation method thereof

    CN117844018A

  • Polyimide resin, polyimide thin film and preparation method therefor, and flexible device

    WO2023098424A1